Production of xylanases by Bacillus subtilis E44 under submerged fermentation conditions - Matos, Madyu; Valdivia, Aymara; Rodríguez, Zoraya; Bocourt, R.; Brizuela, María A.; Portilla, Yadileiny; Rubio, Yasmary; Ramírez, H. L. (Cuban Journal of Agricultural Science, 2018)
Production of xylanases from microorganisms is useful for animal feeding. The objective of this research was to evaluate the xylanase production ability of Bacillus subtilis E44 strain under submerged fermentation conditions. Bacteria were inoculated in Petri dishes with beech xylan (1 %), and the production of xylanases was determined at 24, 48, 72 and 96 h. The formation of clear zones around the colonies after the revelation with Congo red 0.5 %, confirmed the production of enzymes by the strain, and the highest hydrolysis halo (24.7 mm ± 0.57) was obtained at 72 h. Power index showed significant differences for the evaluated times, the best was 4.59 at 72 h. Cellular growth and xilanase production by B. subtilis E44 under submerged fermentation was evaluated for 24 hours in a minimum medium with beech xylan salts and nutrient broth. The maximum activity of xylanases was 0.326 U/mL, at the end of the exponential phase of the culture in a minimum medium of salts plus xylan and 0.130 U/mL in a nutrient broth. Maximum production of xylanases was obtained at 12 h during the submerged fermentation and coincides with the decrease of proteolytic activity of Bacillus subtilis E44. The results show the ability of Bacillus subtilis E44 of expressing xilanase enzymes with the use of beech xylan as a carbon source under submerged culture conditions. These enzymes could improve quality of diets used for monogastric animals. Keywords: enzymes, hydrolysis halo, power index, enzyme activity